Fibrinolytic for treatment of intraventricular hemorrhage: A meta-analysis and systematic review. Issue 1 (January 2018) - Baker, Alexandra Delaney; Rivera Perla, Krissia Margarita; Yu, Zhiyuan; Dlugash, Rachel; Avadhani, Radhika; Mould, William Andrew; Ziai, Wendy; Thompson, Richard E; Staykov, Dimitre; Hanley, Daniel F
Background: Intraventricular hemorrhage is a significant cause of mortality and morbidity worldwide. Treating intraventricular hemorrhage with intraventricular fibrinolytic therapy via a catheter is becoming an increasingly utilized intervention. Aims: This meta-analysis aimed to investigate the role of intraventricular fibrinolytic treatment in hypertensive intraventricular hemorrhage patients and evaluate the effect sizes for survival as well as level of function at differing time points. Summary of review: PubMed, CNKI, VIP, and Wanfang were searched using the terms "IVH" and "IVH and ICH" for human studies with adult patients published between January 1950 and July 2016. Seventeen publications were selected. Data analysis showed lower rates of mortality in the treatment group at 30 days ( P < 0.001), 180 days ( P = 0.001), 365 days ( P = 0.40), and overall ( P < 0.001). Pooling modified Rankin Scale and Glasgow outcome scale data, the treatment group had more good functional outcomes at 30 days ( P = 0.38), 90 days ( P = 0.04), 180 days ( P = 0.31), 365 days ( P = 0.76), and overall ( P = 0.02). Good functional outcome was defined as modified Rankin Scale score of 0 to 3 or a Glasgow outcome scale score of 3 to 5. Conclusions: Intraventricular fibrinolytic for treatment of hypertensive intraventricular hemorrhage reduces mortality and potentially leads to an increased number of good functional outcomes. Different functional outcome scales (modified Rankin Scale or Glasgow outcome scale) produce different effect sizes. Intraventricular fibrinolytic treatment may offer intraventricular hemorrhage patients a targeted therapy that produces meaningful mortality benefit and possible functional outcome benefits.